2000
DOI: 10.1001/archpsyc.57.8.729
|View full text |Cite
|
Sign up to set email alerts
|

A Serotonin Transporter Gene Promoter Polymorphism (5-HTTLPR) and Prefrontal Cortical Binding in Major Depression and Suicide

Abstract: A diffuse reduction of 5-HTT binding in the PFC of individuals with major depression may reflect a widespread impairment of serotonergic function consistent with the range of psychopathologic features in major depression. The localized reduction in 5-HTT binding in the ventral PFC of suicides may reflect reduced serotonin input to that brain region, underlying the predisposition to act on suicidal thoughts. The 5-HTTLPR genotype was not related to the level of 5-HTT binding and does not explain why 5-HTT bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
306
5
9

Year Published

2000
2000
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 558 publications
(341 citation statements)
references
References 124 publications
21
306
5
9
Order By: Relevance
“…The frontal cortex has been the most widely studied brain region, while numerous other brain regions have received less attention. Within the frontal cortex, researchers have found decreases (Stanley et al, 1982;Crow et al, 1984;Arato et al, 1991;Laruelle et al, 1993;Arango et al, 1995;Mann et al, 2000), increases (Meyerson et al, 1982), and no alterations in the SERT binding of suicides Meltzer, 1989, 1991;GrossIsseroff et al, 1989;Lawrence et al, 1990aLawrence et al, , b, 1997Lawrence et al, , 1998Hrdina et al, 1993;Little et al, 1997;Rosel et al, 1997Rosel et al, , 1998Du et al, 1999;Bligh-Glover et al, 2000). Studies in which SERT binding was measured in various other brain regions of suicide victims have produced similar discordant results (Paul et al, 1984;Owen et al, 1986;Gross-Isseroff et al, 1989;Hrdina et al, 1993;Laruelle et al, 1993;Dean et al, 1996;Mann et al, 1996;Lawrence et al, 1997;Little et al, 1997;Rosel et al, 1997Rosel et al, , 1998.…”
Section: Introductionmentioning
confidence: 94%
“…The frontal cortex has been the most widely studied brain region, while numerous other brain regions have received less attention. Within the frontal cortex, researchers have found decreases (Stanley et al, 1982;Crow et al, 1984;Arato et al, 1991;Laruelle et al, 1993;Arango et al, 1995;Mann et al, 2000), increases (Meyerson et al, 1982), and no alterations in the SERT binding of suicides Meltzer, 1989, 1991;GrossIsseroff et al, 1989;Lawrence et al, 1990aLawrence et al, , b, 1997Lawrence et al, , 1998Hrdina et al, 1993;Little et al, 1997;Rosel et al, 1997Rosel et al, , 1998Du et al, 1999;Bligh-Glover et al, 2000). Studies in which SERT binding was measured in various other brain regions of suicide victims have produced similar discordant results (Paul et al, 1984;Owen et al, 1986;Gross-Isseroff et al, 1989;Hrdina et al, 1993;Laruelle et al, 1993;Dean et al, 1996;Mann et al, 1996;Lawrence et al, 1997;Little et al, 1997;Rosel et al, 1997Rosel et al, , 1998.…”
Section: Introductionmentioning
confidence: 94%
“…68,[70][71][72][73] However, the translation of in vitro findings into in vivo functioning does not appear straightforward. Human neuroimaging studies of 5-HTT availability [74][75][76][77][78][79] and post-mortem studies of 5-HTT bindings and rRNA expression [80][81][82] have not detected any consistent effect of 5-HTTLPR. No reliable association was found between 5-HTLPR and the level of serotonin metabolite in the cerebrospinal fluid.…”
Section: The Functionality Of 5-httlprmentioning
confidence: 99%
“…The next of kin consented to tissue collection, review of relevant records, and a psychological autopsy (see Mann et al, 2000) for description of psychological autopsy procedures). All cases died suddenly.…”
Section: Subjectsmentioning
confidence: 99%
“…Neuroendocrine studies find blunted serotoninmediated prolactin release related to aggressive and suicidal behavior (see Dulchin et al, 2001;Malone et al, 1996;Weiss and Coccaro, 1997). Furthermore, in postmortem serotonin receptor-binding studies, presynaptic alterations are identified in the brainstem (Arango et al, 2001) and pre-and postsynaptic alterations are described in the prefrontal cortex (Arango et al, 1995;Hrdina et al, 1993;Mann et al, 2000;Pandey et al, 2002).…”
Section: Introductionmentioning
confidence: 99%